The Role of Long Non-Coding RNAs in Intracranial Aneurysms and Subarachnoid Hemorrhage - Gareev, Ilgiz (Life (Basel), 2020)
Intracranial aneurysms (IAs) represent the most complex and relevant problem of modern neurology and neurosurgery. They serve as one of the main causes of non-traumatic subarachnoid hemorrhage (SAH), causing up to 85% of all cases of intracranial hemorrhage, which is associated with frequent disability and high mortality among patients. Unfortunately, the molecular mechanisms of the development and rupture of IAs are still under study. Long non-coding RNAs (lncRNAs) are non-coding RNAs that typically have a length of more than 200 nucleotides. It is known that lncRNAs regulate many processes, such as transcription, translation, cell differentiation, regulation of gene expression, and regulation of the cell cycle. In recent years, a lot of evidence has established their role in human diseases from oncology to cardiovascular disease. Recent studies have shown that lncRNAs may be involved in the pathogenesis of IAs. The study of lncRNAs and its targets in various pathological conditions of a person is a rapidly developing field, and it is likely that the knowledge obtained from these studies regarding the pathogenesis of intracranial aneurysms will have the potential to use lncRNAs in therapy, as well as in the diagnosis and prediction of high aneurysms risk of rupture.